ASSESSMENT OF HEAVY METALS IN NKOHO RIVER RECEIVING PAINT EFFLUENT, ABIA STATE, NIGERIA - NWAKANMA, A; KANU, C. (Nigerian Journal of Fisheries, 2017)
The study aimed to assess the potential impact of industrial effluents from Saclux Paint Industryon the recipient waterquality of Nkoho River in Abia state. Samples were taken at the effluent discharged point, upstream and downstream of the discharge point. The sample collection points were geo-referenced using Global Positioning system (GPS). Results of heavy metal concentration such as Iron (Fe), Zinc (Zn), Manganese (Mn), Cadmium (Cd), Nickel (Ni), Lead (Pb), Chromium (Cr) and Copper (Cu) at different points in water and in the effluent were estimated using Atomic Absorption Spectrophotometer (AAS). The heavy metal content in the samples varied significantly (p<0.05) between the sampling points. Concentrations of the heavy metals fluctuated during the study period but were constantly higher than the permissible limits by Federal Ministry of Environment and World Health Organisation. These few cases of failure among many could be attributed to possible improper treatment of the effluent prior to discharge into the environment. In conclusion, it was observed that the poor quality of the water occasioned by the further deterioration by the entrance of the paint effluents which confer potentials of health hazards to users of the water.